On the localization of surface waves in the layer of an ideal compressible fluid interacting with the elastic half-space - Bahno О.М. (Reports of the National Academy of Sciences of Ukraine, 2018)
The propagation of quasi-Lamb waves in the system "layer of ideal compressible liquid — elastic half-space" is studied, by using the three-dimensional equations of the classical elasticity theory for a solid body and the linearized Euler equations for a fluid. The dispersion curves for normal waves over a wide range of frequencies are constructed. The influence of the thickness of the layer of an ideal compressible fluid on the dispersion of the phase velocity of quasi-Lamb modes in a hydroelastic waveguide is analyzed. The localization properties of the surface waves in elastic-fluid waveguides are studied. The numerical results obtained are presented in the form of plots and analyzed.